Histology and immunohistochemistry studies on heavy metals pollution in different sizes of catfish in Kuala Gula and Bagan Lalang, Malaysia - Mohammed Nasser Ahmed, Amani (2019)
Heavy metals pollution is a serious issue globally, mainly as results of human activity. Although there are numerous studies on heavy metal pollution in Malaysia, the awareness of the public to the threat of heavy metals is still low. This could be due to most of the reports are solely based on metal concentration but not on the actual damage to the tissues and organ like lung damaged lung photo shown in antismoking campaign. The level of essential and non-essential heavy metal (Zn, Cu, Cd, and Pb) in the water; sediments; in two different species of fish of different sizes, and in different organs were studied. The objectives of this study are: to assess the heavy metals concentration in the water and sediment, to assess the level of heavy metals Zn, Cu, Pb and Cd in different sized and different organs of two catfish species Arius thalassinus and Plotosus anguillaris; to study impact of heavy metal pollution using histopathological changes and finally to demonstrate the expression stress of metallothionein3 in some tissues of the fish using immunohistochemistry technique. Thirty samples of water and sediments samples were obtained from two river plus thirty samples of each species catfish Arius thalassinus and Plotosus anguillaris of small, medium and large sizes caught by fisherman from Kuala Gula and Sepang Besar from April 2015 to December 2017. Water, sediments and fish samples were handled following the standard method for analyzing heavy metals. Heavy metals were determined using AAS. The records of fish weigh and length were taken and graded according to small, medium and large fish. Muscle, stomach, gills, liver, and kidney were separated to determine heavy metals concentration, histology and immunohistochemistry analysis. Tissues were processed following standard histological procedures and immunohistochemistry technique. The results showed the concentration of heavy metals in water and sediment was still with the range. The mean concentration of metals in water of Kuala Gula and Sepang Besar were Zn: (0.3 & 0.02 mg/L); Cu: (0.1 & 0.04 mg/L); Pb: (0.32 & 0.30 mg/L) and Cd: (0.40 & 0.01 mg/L). The concentration of metals in sediment of Kuala Gula and Sepang Besar were Zn: (39.20 & 39.90 μg/g dry.wt); Cu: (20.10 & 13.10 μg/g dry.wt); Pb: (18.90 & 15.20 μg/g dry.wt) and Cd: (1.40 & 1.80 μg/g dry.wt) in two rivers respectively. The findings in this study recorded that Arius thalassinus and Plotosus anguillaris were contaminated with Zn, Cu, Pb, and Cd. Large catfish showed higher accumulation for heavy metals in two species catfish followed medium and small fish. Kidney in large Arius thalassinus showed a high score in Zn with mean 284.0±29.7μg/g dry.wt and liver showed high score of accumulation of heavy metals in Zn also in large fish Plotosus anguillaris 120.30±2.4μg/g dry.wt. The muscles had the lowest metals concentration in both species catfish. Muscle recorded the lowest Cd accumulation with mean (0.61±0.05& 0.51±0.03μg/g dry.wt.) in Arius thalassinus and Plotosus anguillaris respectively. Histopathological alterations were observed including degeneration with necrosis in liver, and kidney, proliferation in the epithelium of gill filaments and fusion of secondary lamellae. The severity of histopathological alteration corresponds to increasing metals concentration in the gill, liver, and kidney. Antibodies showed a positive cross reactivity with MT3 proteins. MT3 immune reaction was high for Zn, Cu, Pb and Cd in kidney, liver, and gills. MT3 localization/induction expression upon exposure to Zn, Cu, Pb, and Cd can be demonstrated using immunohistochemistry in the cytoplasm, nuclei, renal tubules, melano-macrophage centres; hepatocytes, cytoplasm, nuclei melano-macrophages centre; filaments, cartilage, and basal membrane in the gills. There were positive relationship between MT3 and concentration of Zn, Cu, Pb, and Cd in this study. This study concluded that the high concentration of heavy metals in tissues of Arius thalassinus and Plotosus anguillaris affect them negatively. The different MT3 expressions in different sized fish and different polluted place showed the potential use MT3 as biomonitoring biomarker for heavy metals exposure in an aquatic environment. Present study showed that the two species of catfish Arius thalassinus and Plotosus anguillaris are good candidate for biological indicator and have ability to accumulate heavy metals. Histopathology techniques and immunohistochemistry with MT3 gave clearer picture on the impact of heavy metal on tissues and cells. The non parametric collective rank and score analysis are able to revealed the trend of heavy metal accumulation and impact of heavy metals concentrations based on metals species, different location, fish species, size of fish and different organs.